2006
DOI: 10.1007/s00586-006-0227-4
|View full text |Cite
|
Sign up to set email alerts
|

Back posture education in elementary schoolchildren: a 2-year follow-up study

Abstract: Within the scope of primary prevention regarding back functioning in children, research on the stability of intervention effects is indispensable. Along this line, the transition from childhood to adolescence is an important phase to evaluate the potential stability of intervention effects because of the typically mechanical and psychological demands related to adolescence. The main aim of the current study was to investigate the effects of a back education program at 2-year follow-up, in youngsters aged 13-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
2
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 32 publications
3
41
2
8
Order By: Relevance
“…The results of similar intervention studies 14,35 show a lower tendency for correct answers for most of the questions directly compared to those of the present study. The greater differences between the studies were found for those questions related to handling of materials and spinal curves.…”
Section: Discussioncontrasting
confidence: 31%
See 1 more Smart Citation
“…The results of similar intervention studies 14,35 show a lower tendency for correct answers for most of the questions directly compared to those of the present study. The greater differences between the studies were found for those questions related to handling of materials and spinal curves.…”
Section: Discussioncontrasting
confidence: 31%
“…During school years, children spend one third of their waking hours at school 9 , an environment that can expose them to ergonomic risk factors including carrying heavy backpacks, sitting postures for prolonged periods, and inadequate furniture [10][11][12][13] . Thus, the school is a potential environment for developing musculoskeletal disorders, as well as implementing back care programs 14 . Various postural deviations, especially of the spine, originate during childhood and adolescence 12,[15][16] , which is a period of rapid musculoskeletal development (growth spurt) and when the spine is more susceptible to deformities 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The life goal of schoolchildren is to play, therefore any pain that deprives them of that is a source of worry 8 . Preventive training programs that combine education and movement have good repercussion as a form of improving posture [9][10][11][12][13][14] . Meta-analyses show evidence of a decrease in chronic low back pain after a training program known as Back School 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Geldhof et al 31 avaliaram um programa educativo que foi aplicado entre os escolares e consistiu de 13 horas de educação das costas com o argumento de promover a boa mecânica corporal e aumentar o dinamismo postural na classe. Os resultados após um ano da intervenção mostraram que 96% dos alunos recordaram das sessões sobre educação das costas e que não houve aumento da lombalgia e ou dor na nuca.…”
Section: Discussionunclassified